Factors influencing women's perceptions of shared decision making during labor and delivery: Results from a large-scale cohort study of first childbirth. Issue 6 (June 2018) - Attanasio, Laura B.; Kozhimannil, Katy B.; Kjerulff, Kristen H.
Highlights: Few studies have examined shared decision making in the childbirth context. Obstetric procedure use was associated with less shared decision making. Shared decision making was less common among lower-SES women and women of color. Black women who delivered by cesarean had strikingly low shared decision making. Abstract: Objective: To examine correlates of shared decision making during labor and delivery. Methods: Data were from a cohort of women who gave birth to their first baby in Pennsylvania, 2009–2011 (N = 3006). We used logistic regression models to examine the association between labor induction and mode of delivery in relation to women's perceptions of shared decision making, and to investigate race/ethnicity and SES as potential moderators. Results: Women who were Black and who did not have a college degree or private insurance were less likely to report high shared decision making, as well as women who underwent labor induction, instrumental vaginal or cesarean delivery. Models with interaction terms showed that the reduction in odds of shared decision making associated with cesarean delivery was greater for Black women than for White women. Conclusions: Women in marginalized social groups were less likely to report shared decision making during birth and Black women who delivered by cesarean had particularly low odds of shared decision making. Practice implications: Strategies designed to improve the quality of patient-provider communication, information sharing, and shared decision making must be attentive to the needs of vulnerable groups to ensure that such interventions reduce rather than widen disparities.